Driving errors, estimated performance and individual characteristics under simulated and real road traffic conditions – A validation study. (October 2021) - Faschina, Silvia; Stieglitz, Rolf-Dieter; Muri, Raphaela; Strohbeck-Kühner, Peter; Graf, Marc; Mager, Ralph; Pflueger, Marlon O.
Highlights: Research into the validity of driving simulators requires an integrated approach. Self-reported and observer-rated driving behaviour reflects the performance in the driving simulator. Performance demands in respect of adaptability in the driving simulator may differ from those during a real drive. Cognitive aspects may impact negatively on validity. Abstract: Background: The suitability of driving simulators for the prediction of driving behaviour in road traffic has been able to be confirmed in respect of individual assessment parameters. However, there is a need for overarching approaches that take into account the interaction between various influencing factors in order to establish proof of validity. The aim of this study was to explore the validity of our driving simulator in respect of its ability to predict driving behaviour based on participants' observed driving errors and driver's individual characteristics. Method: 41 healthy participants were assessed both in a Smart-Realo-Simulator and on the road. By means of linear modelling, the correlation between observed driving errors was investigated. In addition, the influence of self-reported and externally assessed driving behaviour as well as individual parameters (education and training; driving history) were analysed. Results: By including these factors, 58% of the variance could be explained. For observed driving errors, a relative validity was established. For self-reported and externally assessed driving behaviour, an absolute to relative validity emerged. The amount of time spent in education and training proved to have a significant influence on driving performance in the simulator, but not on the road. Discussion: In general, our results confirmed the validity of our driving simulator with regard to observed and self-reported driving behaviour. It emerged that education and training as potential indicators of cognitive resources played a differential role regarding the study conditions. Since real road driving is considerably automated in experienced drivers, this result suggests that simulation-related behavioural regulation is challenged by additional cognitive demands as opposed to behavioural regulation extending to real road driving. However, the source of these additional cognitive demands remains currently elusive and may form the subject of future research.